1985
DOI: 10.1093/clinchem/31.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol determination in serum after fractionation of lipoproteins by immunoprecipitation.

Abstract: We investigated the immunoprecipitation of apolipoprotein B-binding lipoproteins, or of apo A-I- and apo C-binding lipoproteins, by delipidated antiserum for measuring cholesterol in the nonprecipitated lipoprotein fractions. After immunoprecipitation of serum with delipidated anti-apo B, we determined by immunoelectrophoresis that no beta- or pre-beta lipoproteins were present, whereas alpha-lipoproteins remained in the supernate. Conversely, after immunoprecipitation with an antiserum against apo A-I + apo C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Problems involved are lack of standardized procedures, lack of reliable quality control materials, changing immunoreactivity due to self-association and aggregation of the particles, varying content of lipid which may mask epitopes, and different affinities of the antisera. Assays and assay modifications have been recently described for apoA-I (350)(351)(352)(353)(354), apoB (352,353,(355)(356)(357)(358), Lp(a) (359), apoC (353), apoC-III (360,361). Reference ranges are not yet well defined, especially those of apolipoproteins (362,363).…”
Section: Analytes Of Clinical Interestmentioning
confidence: 99%
“…Problems involved are lack of standardized procedures, lack of reliable quality control materials, changing immunoreactivity due to self-association and aggregation of the particles, varying content of lipid which may mask epitopes, and different affinities of the antisera. Assays and assay modifications have been recently described for apoA-I (350)(351)(352)(353)(354), apoB (352,353,(355)(356)(357)(358), Lp(a) (359), apoC (353), apoC-III (360,361). Reference ranges are not yet well defined, especially those of apolipoproteins (362,363).…”
Section: Analytes Of Clinical Interestmentioning
confidence: 99%
“…To check the reproducibility and reliability of the methods, the cholesterol content of the sample in one run (Within batch) and after storage at -20˚C for one week (Between batch) were determined. The results showed that the cholesterol value of these determination agreed with each other and within batch and between batch coefficient of variation (CV) were 1.59% & 4.15 % (Table 2), which is quite close to earlier reports such as colorimetric, electrochemical method [26] employing alkyl amine glass bound enzyme (1.6% for intrabatch and 3.2% for interbatch), amperometric method using silica gel bound enzyme (< 1.5% for all samples) [7] and flow injection method employing controlled pore glass bound cholesterol esterase and cholesterol oxidase (within day < 1.0 and between day < 2.5%) [27], measuring cholesterol after precipitation with phosphotugstic acid/MgCl 2 (within day 5.0 % and between day 8.2%) [28] and amperometric detection of cholesterol (within day 2%-between day 4%) [9]. The low coefficient of variation values indicated the accuracy, reproducibility and reliability of the method.…”
Section: Precisionmentioning
confidence: 99%